Screening of antibiotic-producing Streptomyces from marine sediments of Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Antimicrobial resistance is a rising concern in the treatment of infectious diseases and the discovery of potential antimicrobial compounds is needed to combat against it. The focus of this study was the in vitro antimicrobial activities of Streptomyces obtained from the soil samples collected from different places of Cox’s Bazar, Bangladesh. A total of 156 isolates was obtained from thirty soil samples using two selective media namely yeast malt agar and starch casein agar. The isolates were morphologically distinct on the basis of spore mass color, reverse slide color, aerial and substrate mycelia formation and production of diffusible pigment. Among the isolates, 12 exhibited good antimicrobial activity against the tested micro-organisms. Isolates were subjected to biochemical characterization and identified as Streptomyces spp. The results suggest that the Streptomyces species could be a promising source for potential antibacterial agents.